The skeletal maturity of Australian children aged 10–13 years in 2016. (17th February 2021) - Duckham, Rachel L.; Hawley, Nicola L.; Rodda, Christine; Rantalainen, Timo; Hesketh, Kylie D.
Abstract: Skeletal maturity can be used as a biological indicator of the tempo of growth in children and adolescents. We present a description of skeletal maturity from a cohort of white Australian children and describe variation in skeletal maturity based on child age. Participants ( n = 71; age 10.5–13.9 years) were recruited from the 'Healthy, Active Preschool & Primary Years (HAPPY)' study. Left hand-wrist radiographs were used to determine skeletal maturity using the Tanner-Whitehouse III (TW3) RUS technique. In boys, the mean skeletal maturity offset (bone age – chronological age) was −0.12 ± 0.19 years and 57.9% had delayed skeletal maturity compared to chronological age. Among those with delayed skeletal maturity, the average delay was 0.99 years (range 0.02–2.54 years). In girls, skeletal age was advanced, on average, compared to chronological age by 0.32 ± 0.20 years. Among the 39.4% of girls with delayed skeletal maturity, the average delay was 0.48 years (range: 0.01–2.28). Four children in the sample exhibited a delay in skeletal maturity greater than 2 years. In the context of secular trends towards advanced skeletal maturity observed globally, delayed skeletal maturation in this white, economically privileged cohort are surprising and warrant further exploration.